Trends in job skill demands in OECD countries - Handel, Michael J. (Paris, 2012)
"This report examines skill trends in 24 OECD countries over the past several decades. The skill measures used include broad occupation groups, country-specific direct measures of skill requirements from international surveys, and direct skill measures from the Occupational Information Network (O*NET) database applied to both United States and European labour force surveys. Each kind of data has its own strengths and limitations but they tell a consistent story."